The effects of prophylactic and therapeutic interventions of nigella sativa on functional and biochemical markers of muscle damage and inflammation following eccentric exercise - Raimi, Nur Fatihah (2020)
Nigella sativa (NS) is widely known to have anti-inflammatory effects on various inflammation models, however no known study has been done on exerciseinduced muscle damage (EIMD) as a model of inflammation. The first study that has been carried out by the same researchers before was unable to determine the effective dose to enhance recovery following EIMD because the single one-off dose method used in the study failed to affect all measured parameters. Thus, in this study, the method of supplementation was changed from a single one-off dose to prolonged multiple-doses to see the effectiveness of NS on prevention and treatment of EIMD. The objective of this study was to determine the effectiveness of prophylactic and therapeutic interventions of NS in enhancing recovery following exercise. Thirty sedentary men aged 19 to 27 y.o were double-blindedly assigned to 3 groups, either prophylactic (P), therapeutic (T) or control (C). P group administered 2000mg/day of NS daily from 2 weeks before exercise to four days post-exercise, meanwhile T group administered 2000mg/day of NS from 30 min before exercise bout to four days post-exercise. The third group (C group) was a control group, which was administered placebo. They had undergone 10 sets X 10 repetitions of countermovement jump (CMJ) with 30 second rest between each set, employing squat in starting and landing position to facilitate muscle damage. A set of tests were conducted to measure functional markers (muscular power, soreness, tenderness, thigh circumference, range of motion (ROM)) and biochemical markers (blood enzymes (i.e. creatine kinase (CK) and lactate dehydrogenase (LDH)), cytokines (interleukin-6 (IL-6) and interleukin-1β (IL-1β)), and white blood cells (neutrophils and macrophages)) of muscle damage were measured at pre-exercise, 30 minutes, 1, 2, 3 and 4 days post-exercise. Analysis by a mixed-factorial ANOVA showed that no significant interactions were found on muscle power, soreness, tenderness, thigh circumference, range of motion (ROM), creatine kinase (CK), interleukin-6 (IL-6), interleukin-1β (IL-1β) and macrophages between three different groups across the measurement sessions. It means there were no significant differences regardless of which intervention the participants had been given on these parameters. However, there were significant interactions found on lactate dehydrogenase (LDH) and neutrophils between three different groups across the measurement sessions. Lactate dehydrogenase (LDH) and neutrophils count were not so much affected in P group from pre-exercise to post-4 days measurement compared to T and C group, which experienced abrupt decrease and sudden increase in their lactate dehydrogenase (LDH) and neutrophils count. Ingesting NS two weeks prior and continuously until recovery following exercise was found to have benefit in lowering the magnitude of increase in lactate dehydrogenase (LDH) and returning lactate dehydrogenase (LDH) to pre-exercise count faster, compared to ingesting NS on the exercise day until recovery. This explained that NS can speed the recovery process following EIMD if taken two weeks before engaging in exercise until recovery. In conclusion, ingesting NS two weeks prior and continuously until recovery (prophylactically) following exercise was found to have benefit in lowering the magnitude of increase in lactate dehydrogenase (LDH) and neutrophils after EIMD and returning the markers to pre exercise count faster, compared to ingesting NS on the exercise day until recovery (therapeutically), proving that NS can be used as a potential preventive supplement, not as an after-injury treatment.